Search for trilepton resonances from chargino and neutralino pair production in s = 13 TeV pp collisions with the ATLAS detector - Aad, G. (2020)
51 pages in total, author list starting page 35, 9 figures, 4 tables, submitted to Physical Review D. All figures including auxiliary figures are available at http://atlas.web.cern.ch/Atlas/GROUPS/PHYSICS/PAPERS/SUSY-2018-36